Political parties and web 2.0 tools: A shift in power or a new digital Bandwagon? - Spyridou, Lia Paschalia; Veglis, Andreas A. (My University, 2011)
Since the emergence of the e-democracy project putting emphasis on participation, most analyses focused on the opportunity for political parties to reverse top-down and propaganda-style models and engage in conversation with citizens. Despite the objections posed by the normalisation thesis, the opportunities offered by web 2.0 for feeding vox populi into the political process and letting the 'wisdom of crowds' speak are undeniably growing. The study investigates the main communication functions performed by Greek parties online and the level and type of interactivity provided. The findings suggest the development of a hybrid web 1.5 model, while participation ranks low in the agenda of most political parties. © 2011 Inderscience Enterprises Ltd.
Keywords: Digital campaigning; Interactivity; Web 2.0 tools